Effects of explants and culture medium compositions on quality of chrysanthemum ‘Jayanti Agrihorti’ rooted cuttings - Shintiavira, Herni; Pramanik, Dewi; Daniyanti, Ratna Dewi; Pertiwi, Miranti Dian; Rachmawati, Fitri (Jurnal Ilmu Pertanian, 2024)
'Jayanti Agrihorti' is a superior chrysanthemum therefore rooted cuttings quality is required. In vitro propagation increases the rate of propagation and produces true-to-type plants. The research to obtain the best explants and culture medium composition that is capable of producing high-quality plants.  The research was arranged in a randomized complete block design consisting of two factors. The first factor was the explant, including the apical shoot of 0.5 cm, 1.0 cm, and the nodal segment. The second factor was in vitro culture medium composition (CP), consisting of  CP1 (Murashige and Skoog (MS) medium for initiation, followed by MS + 2.5 mg.L⁻¹ gibberellic acid (GA₃) for subculture), CP2 (MS + 0.25 mg.L⁻¹ benzyl amino purine (BAP) for initiation, followed by MS for subculture), CP3 (MS + 0.25 mg.L⁻¹ BAP for initiation, followed by MS + 2.5 mg.L⁻¹ GA₃ for subculture), and CP4 (MS + 0.5 mg.L⁻¹ BAP for initiation, followed by MS + 0.25 mg.L⁻¹ BAP for subculture). Acclimatization was performed after third subculture. The apical shoot size of 0.5−1.0 cm is optimum for producing chrysanthemum-rooted cuttings. Meanwhile, MS medium for initiation stage, followed by MS + 2.5 mg.L⁻¹ GA₃ for subculture is the best culture medium composition for in vitro propagation. This explant and culture medium composition produced higher chlorophyll a, b, and a+b content, thereby resulting in higher plant, more leaves, larger stem diameter, and longer root length. This are recommended for chrysanthemum propagation, particularly in 'Jayanti Agrihorti'.